Orchids of Mount Ungaran (Indonesia) compiled from a decade of data collections between 2010 and 2021: The List of Ungaran Orchids - FIRMAN HERU KURNIAWAN; LUTFIAN NAZAR; RINI ANJARWATI; HERBOWO DWI SASONO; MARGARETA RAHAYUNINGSIH (Nusantara Bioscience, 2021)
Abstract. Kurniawan FH, Nazar L, Anjarwati R, Sasono HD, Rahayuningsih M. 2021. Orchids of Mount Ungaran (Indonesia) were compiled from a decade of data collection between 2010 and 2021. Nusantara Bioscience 13: 238-252. Orchid is well known as a plant group widely used as ornamental plants because of their uniqueness. But, high exploitation, deforestation, and land-use changes have threatened orchid species and triggered extinction. It also happened in Mount Ungaran, Central Java, Indonesia, despite its designation as an essential ecosystem area. This research was conducted to add an updated list of wild orchid species that can serve as biodiversity baseline data for conservation management in Mount Ungaran. The study was carried out through exploration activities from 2010 to 2021. The study area covered 11 sites, i.e., Gentong, Kalisidi, Pasigitan, Banyuwindu, Watuondo, Indrakila, Gonoharjo, Gajahmungkur, Camp Mawar, Gondang, and Puncak, which were all included in the buffer zone of Mount Ungaran. A total of 115 species from 54 genera of orchids were successfully identified, including 78 species of epiphyte and 37 species of terrestrial orchids. Among the species recorded, at least 27 species were known to be endemic to Indonesia, and 8 species were endemic to the island of Java, of which four species were listed in the IUCN Red List. In addition, all the species found were listed in Appendix II of the CITES, except one species, Paphiopedilum javanicum, which was listed in Appendix I. This study recorded the new distribution records of several species of orchids that were previously only found in West Java or East Java, i.e., Ania penangiana, Pholidota convallariae, and Crepidium junghuhnii. This study has also documented a species from the genus Crepidium, which morphological characters have not been described in any identification guides. The Gentong area has the potential as a priority for in-situ orchid protection area of the highest number of species reached 54% of all orchids found on Mount Ungaran.